O emprego juvenil no limiar do século XXI :estudo a partir da RAIS e dos programas de inserção de jovens no mercado de trabalho de Natal/RN - Santos, Varélio Gomes dos (2005)
This study received the title THE JUVENILE EMPLOYMENT IN THE THRESHOLD OF THE XXI CENTURY: study starting from RAIS and of the programs of youths' insert in the labor market of Natal/RN . It presents as main objective to investigate, starting from the officials data of the Ministério do trabalho e emprego - MTE and of the federal and state government programs, the evolution of the formal employment for youths and the difficulties that leads the success of the returned initiatives the youths' insert in the formal market of work in Brazil and in Rio Grande do Norte, in the period from 2000 to 2004. To accomplish the research, it prioritizes the study of the evolution of the formal employment starting from the data of the MTE as form of diagnosing the formal market of the juvenile work. Search a descriptive way to identify the first results of the programs Primeiro Emprego- PPE (federal) and Primeira Chance - PPC (state), to interpret and to identify the existent gaps among the proposal initial of those programs and the first results obtained in the city of Natal. The research has character no-probability and it applies closed questionnaires for youths assisted by the programs. Were interviewed the local representatives of PPE and PPC, besides representatives of the organized civil society all through open structured interview, covering a total of 103 interviews. The results demonstrated that while PPC (state) obtained success inserting youngs, the PPE (federal) just got to insert 1,5% of the amount subsidized by the state program in Natal. That situation demonstrates a clear preference of the companies for PPC (state), in detriment of the federal program